Novel diethanolamine based deep eutectic mixtures for carbon dioxide (CO2) capture: synthesis and characterisation - Murshid, Ghulam; Mjalli, Farouq Sabri; Naser, Jamil; Al-Zakwani, Suaad; Hayyan, Adeeb (Taylor & Francis, 2019)
In this work, diethanolamine was successfully used as a hydrogen bond donor to prepare three different deep eutectic solvents (DESs) using three quaternary ammonium salts at different molar ratios. Important physical properties of the prepared DESs including melting point, glass transition, crystallisation temperature, density, refractive index and viscosity were measured in temperature ranging from (298.15 to 358.15 K). Moreover, in order to explore the changes in chemical structures of the DESs, FTIR analysis was performed. The developed DESs have melting points lower than 293.15 K, and of significantly low density (close to water) and comparable viscosity. The effect of temperature and molar ratio on physical properties were also discussed. Empirical models were used to correlate the density, refractive index and viscosity data of the DESs as a function of temperature and molar ratio. A quantitative analysis, also called as ANOVA analysis, was conducted to investigate the significance of the experimental physical properties data. The new DESs prepared in this work have a potential to be used in numerous applications including CO 2 capture. © 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group.